Superior Haplotypes for Early Root Vigor Traits in Rice Under Dry Direct Seeded Low Nitrogen Condition Through Genome Wide Association Mapping - Anandan, Annamalai; Panda, Siddharth; Sabarinathan, S.; Travis, Anthony J.; Norton, Gareth J.; Price, Adam H. (Frontiers in Plant Science, 2022)
To meet the growing demand for food, water and land have been extensively exploited during the last two decades. The changing climate has prompted rice scientists and farmers of the tropics and subtropics to adopt the direct seeded rice (DSR) system. DSR system of rice cultivation significantly reduces fresh water consumption and labor requirements, while increasing system productivity, resource use efficiency, and reducing greenhouse gas emissions. The successful DSR rice genotype requires early root vigor to achieve a good crop stand by acquiring the required nutrient and water since there is greater competition with weeds. The aus subpopulation which is adapted for DSR was evaluated to understand the biology of early root growth under limited nitrogen conditions over two seasons under two-time points (14 d and 28 d). The correlation study identified a positive association between shoot dry weight and root dry weight. Genome-wide association study was conducted on root traits of 14 and 28 days with 2 million SNPs using an efficient mixed model. QTLs over a significance threshold of P < 0.0001 and a 10% false discovery rate were selected to identify genes involved in root growth related to root architecture and nutrient acquisition from 97 QTLs. Candidate genes under QTLs are explored. On chromosome 4 around 30 Mbp are two important peptide transporters (PTR5 and PTR6) involved in mobilizing nitrogen in the root during the early vegetative stage. In addition, several P transporters and expansin genes with superior haplotypes are discussed. A novel QTL within 21.12 Mb to 21.46 Mb on chromosome 7 with two LD blocks governing root length at 14 days were identified. The QTLs/candidate genes with superior haplotype for early root vigor reported here could be explored further to develop genotypes for DSR conditions.